Compound heterozygous with Hb G-Taipei and Hb Lepore-Boston-Washington: An unexpected finding triggered by HbA1c measurement - Yu Li; Anping Xu; Juan He; Limin Huang; Li Lin; Jie Li; Yong Xia; Ling Ji (Practical Laboratory Medicine, 2024)
Background: Hemoglobin A1c has been widely used to diagnose and monitor diabetes. However, the accuracy of HbA1c analysis can be significantly affected by hemoglobin variants, leading to falsely low or elevated levels and misdiagnosis or inappropriate diabetes management. Case report: In this study, we present the case of a 23-year-old man with undetectable HbA1c levels during his annual checkup by high-performance liquid chromatography (HPLC) and capillary electrophoresis (CE). To investigate the reason for HbA1c absence, Sanger sequencing, multiplex ligation-dependent probe amplification assay (MLPA), long-read single molecule real-time sequencing (SMRT) and MALDI-TOF mass spectrometry (MS) were performed, and the proband was identified as compound heterozygous of β-thalassemia with Hb G-Taipei (HBB:c.68A > G) and Hb Lepore-Boston-Washington (NG_000007.3:g.63632_71046del). Conclusion: The combination of these molecular technologies including MLPA, long-read SMRT sequencing and MALDI-TOF MS is beneficial for identifying rare hemoglobin variants. This case also provides essential evidence for uncovering the effect of compound heterozygosity for Hb Lepore-Boston-Washington and Hb G-Taipei on hematological phenotypes and HbA1c analysis.